A docking interface in the cyclin Cln2 promotes multisite phosphorylation of substrates and timely cell cycle entry - Bhaduri, Samyabrata (Curr Biol, 2015)
BACKGROUND: Eukaryotic cell division is driven by cyclin-dependent kinases (CDKs). Distinct cyclin-CDK complexes are specialized to drive different cell cycle events, though the molecular foundations for these specializations are only partly understood. In budding yeast, the decision to begin a new cell cycle is regulated by three G1 cyclins (Cln1–Cln3). Recent studies revealed that some CDK substrates contain a novel docking motif that is specifically recognized by Cln1 and Cln2, and not by Cln3 or later S- or M-phase cyclins, but the responsible cyclin interface was unknown. RESULTS: Here, to explore the role of this new docking mechanism in the cell cycle, we first show that it is conserved in a distinct cyclin subtype (Ccn1). Then, we exploit phylogenetic variation to identify cyclin mutations that disrupt docking. These mutations disrupt binding to multiple substrates as well as the ability to use docking sites to promote efficient, multi-site phosphorylation of substrates in vitro. In cells where the Cln2 docking function is blocked, we observed reductions in the polarized morphogenesis of daughter buds and reduced ability to fully phosphorylate the G1/S transcriptional repressor Whi5. Furthermore, disruption of Cln2 docking perturbs the coordination between cell size and division, such that the G1/S transition is delayed. CONCLUSIONS: The findings point to a novel substrate interaction interface on cyclins, with patterns of conservation and divergence that relate to functional distinctions among cyclin subtypes. Furthermore, this docking function helps ensure full phosphorylation of substrates with multiple phosphorylation sites, and this contributes to punctual cell cycle entry.